Risk factors for schistosomiasis in an urban area in northern Côte d'Ivoire - Richard K. M'Bra; Brama Kone; Yapi G. Yapi; Kigbafori D. Silué; Ibrahima Sy; Danielle Vienneau; Nagnin Soro; Guéladio Cissé; Jürg Utzinger (BMC, 2018)
Abstract Background Schistosomiasis is a water-based disease transmitted by trematodes belonging to the genus Schistosoma. The aim of this study was to assess the relationship between the prevalence of schistosomiasis and access to water, sanitation and hygiene (WASH) and environmental and socioeconomic factors in the city of Korhogo, northern Côte d'Ivoire. Methods A cross-sectional study including 728 randomly selected households was conducted in Korhogo in March 2015. The heads of the households were interviewed about access to WASH and environmental and socioeconomic factors. All children abed between 5 and 15 years living in the households were selected to provide stool and urine samples for parasitological diagnosis of Schistosoma mansoni and Schistosoma haematobium infection. The relationship between infection with S. mansoni and potential risk factors was analysed by a mixed logistic regression model with 'household' as a random factor. Likelihood ratio tests were used to identify factors that were significantly associated with a Schistosoma spp. infection. Results The overall prevalence of schistosomiasis among school-aged children in Korhogo was 1.9% (45/2341) composed of 0.3% (3/1248) S. haematobium and 3.5% (42/1202) S. mansoni. Due to the low prevalence of S. haematobium infection, risk factor analysis was limited to S. mansoni. Boys were 7.8 times more likely to be infected with S. mansoni than girls. Children between 10 and 15 years of age were 3.8 times more likely to be infected than their younger counterparts aged 5-10 years. Moreover, living in a house further away from a water access point (odds ratio [OR] = 0.29, 95% confidence interval [CI]: 0.13-0.70) and abstaining from swimming in open freshwater bodies (OR = 0.16, 95% CI: 0.04-0.56) were significantly associated with decreased odds of S. mansoni infection. The socioeconomic status did not appear to influence the prevalence of S. mansoni. Conclusions A strategy to reduce the incidence of schistosomiasis should focus on health education to change the behaviour of populations at risk and encourage communities to improve sanitation and infrastructure in order to reduce contact with surface water.